2018
DOI: 10.18805/ijar.b-887
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker-based estimation of the genetic diversity of cattle in Chongqing

Abstract: Cattle are the main source of meat in Chongqing. This study investigated the genetic diversity of cattle native to Chongqing and 4 introduced breeds. A total of 96 individuals from 5 breeds were genotyped using six microsatellite markers. Five markers were highly polymorphic within the breed populations, and one marker had moderate levels of polymorphism. Heterozygosity ranged from 0.5379±0.0434 in Simmental to 0.6667±0.0559 in Charolais. The heterozygosity deficit was significant in all populations analyzed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Likewise, F IT values indicate an overall deficit of heterozygotes in the total population. Ni et al, 2018 also reported positive inbreeding coefficients varying between 0.0017 and 0.0367 in five cattle breeds in China (one native and four introduced breeds) and described a significant deficit in heterozygosity in the studied populations. Between two sheep breeds in India (Nellore and Deccani breeds), the FIS values ranged from -0.372 to 0.74, FST values ranged from 0.001 to 0.172 and FIT values ranged from -0.370 to 0.728 (Amareswari et al, 2018).…”
Section: Detection Of Homologous Loci In Sheep and Cattlementioning
confidence: 71%
See 1 more Smart Citation
“…Likewise, F IT values indicate an overall deficit of heterozygotes in the total population. Ni et al, 2018 also reported positive inbreeding coefficients varying between 0.0017 and 0.0367 in five cattle breeds in China (one native and four introduced breeds) and described a significant deficit in heterozygosity in the studied populations. Between two sheep breeds in India (Nellore and Deccani breeds), the FIS values ranged from -0.372 to 0.74, FST values ranged from 0.001 to 0.172 and FIT values ranged from -0.370 to 0.728 (Amareswari et al, 2018).…”
Section: Detection Of Homologous Loci In Sheep and Cattlementioning
confidence: 71%
“…The study of genetic diversity in three sheep breeds in Tunisia using microsatellite markers also revealed a deficit in heterozygosity (Khaldi et al, 2020). Similarly, Ni et al, 2018 reported a significant heterozygosity deficit in cattle in Chongqing (Ni et al, 2018). The F parameters were Hnb: H calculated without bias (Nei 1978).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Microsatellite markers have been extensively applied to genetic diversity studies of cow (Ni et al, 2018), sheep and poultry (Bai et al, 2016a(Bai et al, , 2016b(Bai et al, , 2016c(Bai et al, , 2017 by virtue of high abundance, good repeatability, co-dominance marker and selective neutrality, It is also widely used in plant genetic diversity research (Yang et al, 2013;Li et al,2017;Guo et al, 2018). Genetic diversity of 17 microsatellite markers in the Sonid Bactrian camel population was analyzed in this study, association analysis of these microsatellite markers with body weight and body size and other traits was conducted, and microsatellite markers associated with body size traits of Sonid bactrian camels was found out so as to provide a reference for marker assisted selection, protection and rational utilization of Sonid bactrian camels.…”
Section: Introductionmentioning
confidence: 99%